Atmospheric chamber to study the effects of ambient parameters on the efficiency of solar cells - Ghahraei, Ali (2014)
Solar energy offers a clean, climate-friendly, very abundant and inexhaustible energy resource for mankind, relatively well-spread over the globe. The efficiency of solar cells is affected by ambient parameters like as irradiance of the sunlight, the angle of the sunlight, ambient temperature and relative humidity. An environmental chamber was developed to simulate implied atmospheric parameters inside the chamber since the availability of various climate condition is hard to be predicted and sometimes is impossible. The irradiance is adjusted automatically by controlling the distance between solar cell’s stand and the sunlight simulator. The angle can be adjusted by designing the solar cell’s stand which can be rotated by a stepper motor. A heater and blower fan was used to change the internal temperature of the chamber. Also, relative humidity can be changed by designed humidifier and de-humidifier. Using the calibration data and provided off-line controller, the amount of irradiance can be set with precision of ~94% of the desired amount and the angle is set between 0° to 90° with maximum error of ±1.1 degree. A Madmani-type fuzzy controller was designed to control the temperature inside the chamber from the laboratory temperature until 60°C with the maximum steady-state error was obtained as 0.3 °C. The amount of relative humidity can be controlled between ~45% and 100% at 26°C to between ~29% and ~81% at 50°C by using a Mamdani-type fuzzy controller. The maximum steady-state error of RH controller was obtained as 1.4%from the experimental results. All of the atmospheric parameters can be controlled by designed interface circuits, data acquisition module and provided computer software. All of the software were developed with LABVIEW platform. The efficiency parameters can be calculated directly from the I-V curve obtained by the embedded source measurement unit and will be saved for further process by using the software.